Population genetics of the FRAXE and FRAXF GCC repeats, and a novel CGG repeat, in Xq28. - Ritchie, R; Chakrabarti, L; Knight, S; Harding, R; Davies, K (1997)
Most of the rare folate sensitive fragile sites cloned to date arise from expansion of a CGG:CCG trinucleotide repeat array. Analysis of the CAG repeat at the Huntington Disease (HD) locus showed a positively skewed repeat distribution leading to the proposal that microsatellites are subject to a mutational bias toward expansion. Such a mutational bias predicts an increase in mean repeat size at all microsatellite loci. We present an analysis of repeats at two fragile site loci, FRAXE and FRAXF, and a novel CGG repeat in Xq28, in five different human populations, which suggests that these loci may also be subject to the same mutation process. The novel repeat array may represent the first evidence for the existence of a fourth fragile site in Xq27.3-28.